If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 39 = 16y Reorder the terms: 39 + 3y = 16y Solving 39 + 3y = 16y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-16y' to each side of the equation. 39 + 3y + -16y = 16y + -16y Combine like terms: 3y + -16y = -13y 39 + -13y = 16y + -16y Combine like terms: 16y + -16y = 0 39 + -13y = 0 Add '-39' to each side of the equation. 39 + -39 + -13y = 0 + -39 Combine like terms: 39 + -39 = 0 0 + -13y = 0 + -39 -13y = 0 + -39 Combine like terms: 0 + -39 = -39 -13y = -39 Divide each side by '-13'. y = 3 Simplifying y = 3
| 8(w+9)=7w-2 | | 3/7x+4 | | (32.50x+3.30)+5.90=220.70 | | -9/4-1/5u=-8/3 | | T=gr+g*vtforg | | 2/3x+8=-2 | | N+3+n+6=-(n+3)+5(1+2n) | | 1/3(a-6)=28 | | y=1/4x-20 | | 2/3x+8=-2 | | 4c+17.2=6c+10.8 | | 2x-12=-2(x-2) | | -20=(-4x)-6x | | 16c+11c+14=95 | | 7(4-3z)=-8(2z-1) | | X-u=5 | | -8(w+6)=-5w-39 | | 35=-6(2p-5) | | 4(2j-5)=3j+10 | | -11+6a=-12(a-6)-9(-a+8) | | 4x^3+23x-2x=0 | | 3/4x-8=91 | | -3x-6=6(x+2) | | 20x-3(5x+4)-11=233 | | 99+65x=261.50 | | 5a+3-a=7 | | 0.1-0.01(x+2)=-0.05(2-x) | | x/-3+10=18 | | 2x+8=3x-5(x+4) | | 6x+8-3x=-16 | | (x^2-3)(x^2-3)+4=-4(x^2-3)-4 | | 891=L(1-0.10) |